Awareness and practice of computer-related ergonomics among resident doctors (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below:The present study was designed to see the level of awareness and practice of computer-related ergonomics among resident doctors. A total of 227 residents participated in this study who had used a computer for at least a year.  They were selected by simple random sampling. A self-reporting questionnaire was used to conduct the study. For better understanding and convenience, the responses were categorized into good, fair, and poor. Awareness level was good in only 15% (n= 34) of residents, fair in 16.7% and the majority 68.3% (n= 155) of residents had a poor level of awareness about ergonomics.